The Implementation of Curriculum at Kuttab Al-Fatih Surabaya - Muhammad Yudo Agression of Akbari; Rahmad Salahuddin (Proceedings of The ICECRS, 2021)
This research describes the concept of the kuttab curriculum during the ancient time and its implementation at the lembaga pendidikan kuttab al-fatih surabaya as part of the national education system. this research is qualified as a special study approach. the data is collected using interview, observation and documents. whereas in analyzing data it uses the concept of analysis of miles and huberman, which is data reduction, data presentation and making conclusion. this research concludes that: 1. formerly the concept of the kuttab curriculum during the ancient time was made only to wish for allah's blessing but later developed to have a social and even material aim. also the content of its curriculum is very simple and uses a separate curriculum pattern. 2. the concept of the kuttab curriculum which is applied at the lembaga pendidikan kuttab al- fatih surabaya contains the aim and contents of the curriculum, teaching method and the system of evaluation as well. kuttab al-fatih educational institution surabaya also uses an informal education (pusat kegiatan belajar masyarakat/pkbm) in applying its educational program by creating an equivalence program in order to achieve the primary education diploma known as the package a diploma as part of the national education which is available in indonesia.